Assessment of the digestibility of some Mediterranean shrubs by in vitro techniques - Ammar, H; López, S; González, J S (Animal Feed Science and Technology, 2005)
The nutritive value of some Mediterranean browse species collected in Tunisia was studied on the basis of their chemical composition, in vitro digestibility and fermentation kinetics (gas production technique). The browse species evaluated were Arbutus unedo, Calicotome villosa, Erica arborea, Myrtus communis, Phillyrea angustifolia, Pistacia lentiscus and Quercus suber. Species varied widely in crude protein content (55–221 g/kg DM), condensed tannins (1–360 g/kg DM), digestible dry matter (DM) (523–681 g/kg DM), asymptotic gas production (187–343 ml/g DM) and fractional gas production rate (0.030–0.047 h−1 ). Based on their in vitro digestibility and fermentation kinetics, species could be clustered in two groups of fodder resources, one of medium-high digestibility including the species M. communis, C. villosa, Ph. angustifolia and A. unedo and another group of low digestibility comprising the species P. lentiscus, Q. suber and E. arborea. The in vitro digestibility and gas production parameters were negatively correlated with phenolic compounds, in particular condensed tannins, suggesting that these in vitro techniques can be appropriate for detecting the presence of anti-nutritional substances in shrubs
Keywords: Gas production; In vitro digestibility; Nutritive value; Shrubs; Tannins